From Models of Capitalism to Models of Regulation: Comparing the United States and China in Regulating Artificial Intelligence - Tonev, Danko (UNWE Yearbook, 2024)
This publication compares the regulatory approaches to artificial intelligence (AI) in the national institutional context of the United States and China. Through comparative normative analysis it is demonstrated that China has been ahead to adopt more binding AI regulations than the U.S., which relies on a less centralized and more market governed and ethical approach. This observation corresponds to the two different capitalist economic models – ‘liberal’ in the United States and ‘state-permeated’ in China, according to the Varieties of Capitalism (VoC) comparative literature. The risk of AI overdevelopment has brought the two global economies closer to attempting to adopt risk-averse domestic regulations and seeking global partnerships for regulating AI global diffusion. Future competition between the two technologically most savvy nations is expected in promoting their own standardized values and practices and in inspiring further academic research.
Keywords: Artificial intelligence; Capitalist мodels; Regulation